Engineering triacylglycerol accumulation in duckweed (Lemna japonica). Issue 2 (16th November 2022) - Liang, Yuanxue; Yu, Xiao‐Hong; Anaokar, Sanket; Shi, Hai; Dahl, William B.; Cai, Yingqi; Luo, Guangbin; Chai, Jin; Cai, Yuanheng; Mollá‐Morales, Almudena; Altpeter, Fredy; Ernst, Evan; et al.
Summary: Duckweeds are amongst the fastest growing of higher plants, making them attractive high‐biomass targets for biofuel feedstock production. Their fronds have high rates of fatty acid synthesis to meet the demand for new membranes, but triacylglycerols (TAG) only accumulate to very low levels. Here we report on the engineering of Lemna japonica for the synthesis and accumulation of TAG in its fronds. This was achieved by expression of an estradiol‐inducible cyan fluorescent protein‐ Arabidopsis WRINKLED1 fusion protein ( CFP‐AtWRI1 ), strong constitutive expression of a mouse diacylglycerol:acyl‐CoA acyltransferase2 ( MmDGAT ), and a sesame oleosin variant ( SiOLE(*) ). Individual expression of each gene increased TAG accumulation by 1‐ to 7‐fold relative to controls, while expression of pairs of these genes increased TAG by 7‐ to 45‐fold. In uninduced transgenics containing all three genes, TAG accumulation increased by 45‐fold to 3.6% of dry weight (DW) without severely impacting growth, and by 108‐fold to 8.7% of DW after incubation on medium containing 100 μm estradiol for 4 days. TAG accumulation was accompanied by an increase in total fatty acids of up to three‐fold to approximately 15% of DW. Lipid droplets from fronds of all transgenic lines were visible by confocal microscopy of BODIPY‐stained fronds. At a conservative 12 tonnes (dry matter) per acre and 10% (DW) TAG, duckweed could produce 350 gallons of oil/acre/year, approximately seven‐fold the yield of soybean, and similar to that of oil palm. These findings provide the foundation for optimizing TAG accumulation in duckweed and present a new opportunity for producing biofuels and lipidic bioproducts. Abstract : Triacylglycerol accumulation in duckweed ( Lemna japonica ) increased by 108‐fold to 8.7% of dry weight upon the expression of an inducible CFP‐ Arabidopsis WRI1, along with constitutive expression of mouse DGAT2 and a variant sesame OLEOSIN.